Pengaruh Perkembangan Modern Sikap Berwirausaha terhadap Keberhasilan UMKM Warung Mie Aceh di Kota Medan - Irwan Tambunan; Faiz Ahmad Sibuea (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
UMKM in Indonesia are a very important part of the country's economic system. The role of UMKM has a major impact on Indonesia's economic growth. UMKM have made a significant contribution, accounting for 60.5% of Indonesia's Gross Domestic Product (GDP). Additionally, UKMs are the largest employer in the country, accounting for approximately 96.9% of total national employment. (Ministry of Cooperatives and UKMs, 2023). The research methodology employed in this study combines qualitative and quantitative approaches. The study was conducted in the city of Medan. The research location was selected through purposive sampling. The population in this study consists of all Aceh Noodle Stall UMKM under the guidance of the Cooperative and UKM Agency in the city of Medan, totaling 30 UMKM. Data processing and analysis were conducted using Structural Equation Modeling -Partial Least Squares (SEM-PLS) using the SmartPLS program. The results of the reliability tests measured using Cronbach's Alpha and composite reliability showed values above 0.7 for each variable and indicator, indicating that all indicators of the variables “Modernization of Entrepreneurial Attitude” and “Business Success” have reliable instruments.